2020
DOI: 10.1002/iub.2401
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis: Unifying model of domain architecture for conventional and novel protein kinase C isozymes

Abstract: Protein kinase C (PKC) family members are multi‐domain proteins whose function is exquisitely tuned by interdomain interactions that control the spatiotemporal dynamics of their signaling. Despite extensive mechanistic studies on this family of enzymes, no structure of a full‐length enzyme that includes all domains has been solved. Here, we take into account the biochemical mechanisms that control autoinhibition, the properties of each individual domain, and previous structural studies to propose a unifying mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…To illuminate how SCA14 mutants might interfere with autoinhibition, we mapped mutations in the C1B and kinase domains on the PKCγ model, generated using the previously published model of PKCβII as a prototype (16). Indeed, many of these mutations exist in domains and at interfaces expected to interfere with autoinhibition of the kinase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To illuminate how SCA14 mutants might interfere with autoinhibition, we mapped mutations in the C1B and kinase domains on the PKCγ model, generated using the previously published model of PKCβII as a prototype (16). Indeed, many of these mutations exist in domains and at interfaces expected to interfere with autoinhibition of the kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we used a homology model for the architecture of conventional PKC isozymes (16) to predict where the 54 known SCA14-associated mutations (Fig. 1A) would occur within the 3dimensional structure of PKCγ (Fig.…”
Section: Age Of Sca14 Onset Inversely Correlates With the Degree Of Impaired Pkcγ Autoinhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…A partial crystal structure of PKCβII was previously solved, however multiple domains remained unresolved due to inadequate electron density (Leonard et al, 2011). Refining this structure, Leonard and others concluded that conventional and novel PKC isozymes share a common 3D architecture, (Jones et al, 2020;Pilo et al, 2022), showing kinase domain as cyan surface, and the C1 domains and C2 domains in ribbon representation. SCA14 mutations, represented as red spheres, are concentrated in C1B domain or interfaces with the kinase domain.…”
Section: Pkc Isozymes Share a Common 3d Architecturementioning
confidence: 99%
“…Arrows indicate linker direction. (C) Hypothetical model of PKCγ structure based on the previously published model for general architecture of PKC isozymes ( Jones et al, 2020 ; Pilo et al, 2022 ), showing kinase domain as cyan surface, and the C1 domains and C2 domains in ribbon representation. SCA14 mutations, represented as red spheres, are concentrated in C1B domain or interfaces with the kinase domain.…”
Section: Introductionmentioning
confidence: 99%